1993
DOI: 10.1128/aac.37.8.1711
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of rufloxacin and ciprofloxacin on T-cell subsets and tumor necrosis factor production in mice infected with Bacteroides fragilis

Abstract: We investigated the in vivo effects of rufloxacin and ciprofloxacin on T-cell subsets and tumor necrosis factor production in mice infected with Bacteroidesfiagiis. These quinolones did not alter the helper/suppressor ratio but did modulate the kinetics of tumor necrosis factor production in infected animals. This result correlated with the observed therapeutic efficacies of the quinolones.Several recent reports indicate that quinolone antibiotics at clinically achievable levels modulate the in vitro growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In vivo studies have demonstrated that trovafloxacin, rufloxacin, and ciprofloxacin have significant anti-inflammatory activities in animal models of intra-abdominal infections caused by anaerobic organisms (with the drugs being devoid of activity against anaerobic organisms) or abscesses induced by heat-killed bacteria. It was demonstrated in those studies that the drugs have significant anti-TNF-␣ effects (14,39,40). In clinical settings it is worthwhile to mention the effect of ciprofloxacin on Crohn's disease, which is partly attributed to TNF-␣ inhibition by the drug (36).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have demonstrated that trovafloxacin, rufloxacin, and ciprofloxacin have significant anti-inflammatory activities in animal models of intra-abdominal infections caused by anaerobic organisms (with the drugs being devoid of activity against anaerobic organisms) or abscesses induced by heat-killed bacteria. It was demonstrated in those studies that the drugs have significant anti-TNF-␣ effects (14,39,40). In clinical settings it is worthwhile to mention the effect of ciprofloxacin on Crohn's disease, which is partly attributed to TNF-␣ inhibition by the drug (36).…”
Section: Discussionmentioning
confidence: 99%
“…On day 11, animals were sacrificed and T-cell subsets, TNF production and bacterial counts were quantitated. As these two fluoroquinolones are inactive against B. fragilis in vitro, their in vivo efficacy is most likely due to immunomodulatory effects [59]. In addition, the MICs surpass 2-to 5-fold the peak concentrations of the two FQs.…”
Section: In Vivo Studies -Intra-abdominal Infectionsmentioning
confidence: 98%
“…1) is a new oral 6-fluoroquinolone with a broad spectrum of activity against gram-negative and grampositive aerobic bacteria and some intracellular pathogens, including Chlamydia pneumoniae and Legionella pneumophila (10,23,36). In vitro, the antibacterial activity of rufloxacin is similar to that of norfloxacin (36), while in animal models it has activity similar to that of ciprofloxacin (12). In humans pharmacokinetic studies have demonstrated that rufloxacin is eliminated slowly, with a half-life in plasma of about 35 h (14,19,37).…”
mentioning
confidence: 94%